2014
DOI: 10.19173/irrodl.v15i1.1651
|View full text |Cite
|
Sign up to set email alerts
|

Initial trends in enrolment and completion of massive open online courses

Abstract: The past two years have seen rapid development of massive open online courses (MOOCs) with the rise of a number of MOOC platforms. The scale of enrolment and participation in the earliest mainstream MOOC courses has garnered a good deal of media attention. However, data about how the enrolment and completion figures have changed since the early courses is not consistently released. This paper seeks to draw together the data that has found its way into the public domain in order to explore factors affecting enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
299
4
32

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(344 citation statements)
references
References 7 publications
9
299
4
32
Order By: Relevance
“…Hundreds of thousands of learners and even more enrolled in MOOCs (Jordan, 2014). However, after a short time, this first excitement was followed by frustration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hundreds of thousands of learners and even more enrolled in MOOCs (Jordan, 2014). However, after a short time, this first excitement was followed by frustration.…”
Section: Introductionmentioning
confidence: 99%
“…However, after a short time, this first excitement was followed by frustration. Despite its popularity, the number of MOOC-takers who actually completed a MOOC after enrollment was reported to be very low with dropout rates between 98 and 90% (Jordan, 2014(Jordan, , 2015Koller, Ng, Do, & Chen, 2013;Liyanagunawardena, Parslow, & Williams, 2014;Reich, 2014). Many researchers agreed that the learning circumstances in MOOCs are exceptional (Huin, Bergheaud, Caron, Codina, & Disson, 2016;Koller et al, 2013;Liyanagunawardena et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the retention rate of MOOCs is quite low. It is reported that the average Massive open online courses (MOOCs) completion rate is below 7% [5]. Breslow et al [6] stated that 154,763 students enrolled for their 6.002x Circuits and Electronics course, but merely around 5% of them completed the course and earned a certificate.…”
Section: Introductionmentioning
confidence: 99%
“…It also has positive effect on learners" educational self-efficiency and their learning achievement, it provides wide insight to plan whole process of learning [10] [12]. Cognition factor is related to learners; using to various strategies to perform their learning assignment [13], and affective factor is connected to mental process composed of concentration, interest, investment and effort.…”
Section: Issues Of Mooc Participationmentioning
confidence: 99%
“…Followings <Table 1> are hypothetical constructs per the fundamental definitions. [4], [8], [15], [19] Emphasizing learning environment focused on interaction away from traditional online education a method of MOOC planning and realizing learning environment [6], [8], [14], [16], [19] Changing and Evolving Education System focused on learners factors needed for learning continuity [2], [3], [6], [8], [11], [14] A role of destructive innovation for existing education system a role of MOOC improving existing education system [7], [18], [19] Providing high quality courses to anyone in the dimension of lifelong education a direction of practice in the national and personal dimension [2], [8], [10], [12], [19] 3. Method…”
Section: Issues Of Mooc Participationmentioning
confidence: 99%